Aspiration Thrombectomy After Intravenous Alteplase Versus Intravenous Alteplase Alone. Issue 9 (September 2016) - Mocco, J; Zaidat, Osama O.; von Kummer, Rüdiger; Yoo, Albert J.; Gupta, Rishi; Lopes, Demetrius; Frei, Don; Shownkeen, Harish; Budzik, Ron; Ajani, Zahra A.; Grossman, Aaron; Altschul, Dorethea; et al.
Abstract : Background and Purpose—: Thrombectomy, primarily with stent retrievers with or without adjunctive aspiration, provided clinical benefit across multiple prospective randomized trials. Whether this benefit is exclusive to stent retrievers is unclear. Methods—: THERAPY (The Randomized, Concurrent Controlled Trial to Assess the Penumbra System's Safety and Effectiveness in the Treatment of Acute Stroke; NCT01429350) was an international, multicenter, prospective, randomized (1:1), open label, blinded end point evaluation, concurrent controlled clinical trial of aspiration thrombectomy after intravenous alteplase (IAT) administration compared with intravenous-alteplase alone in patients with large vessel ischemic stroke because of a thrombus length of ≥8 mm. The primary efficacy end point was the percent of patients achieving independence at 90 days (modified Rankin Scale score, 0–2; intention-to-treat analysis). The primary safety end point was the rate of severe adverse events (SAEs) by 90 days (as treated analysis). Patients were randomized 1:1 across 36 centers in 2 countries (United States and Germany). Results—: Enrollment was halted after 108 (55 IAT and 53 intravenous) patients (of 692 planned) because of external evidence of the added benefit of endovascular therapy to intravenous-alteplase alone. Functional independence was achieved in 38% IAT and 30% intravenous intention-to-treat groups ( P =0.52). Intention-to-treat ordinal modified Rankin Scale odds ratio was 1.76 (95% confidence interval, 0.86–3.59; P =0.12) in favor of IAT. Secondary efficacy analyses all demonstrated a consistent direction of effect toward benefit of IAT. No differences in symptomatic intracranial hemorrhage rates (9.3% IAT versus 9.7% intravenous, P =1.0) or 90-day mortality (IAT: 12% versus intravenous: 23.9%, P =0.18) were observed. Conclusions—: THERAPY did not achieve its primary end point in this underpowered sample. Directions of effect for all prespecified outcomes were both internally and externally consistent toward benefit. It is possible that an alternate method of thrombectomy, primary aspiration, will benefit selected patients harboring large vessel occlusions. Further study on this topic is indicated. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01429350. Abstract : Supplemental Digital Content is available in the text.